Government Control and Restriction on Society as Reflected in Nineteen Eighty-Four by George Orwell and Fahrenheit 451 by Ray Bradbury: an Intertextual Reading - Muhammad Septian Haryando (English Department, Faculty of Humanities, Andalas University, 2015)
George Orwell’s Nineteen Eighty-Four and Ray Bradbury’s Fahrenheit 451 are masterpieces of both well-known authors. Both novels highlight government’s control and propaganda upon society as they reveal different ways of control and propaganda in the stories. This research aims to find the intertextual relation that exist in both novels. In conducting this research, the writer uses the theory of intertextuality by Julia Kristeva, combined with the Ideology and Ideological State Apparatus theory by Louis Althusser. The research proves that there are so many similarities between both novels in the terms of the government control purposes such as making people become passive, making people believe what government wants them to believe, and eliminating people’ chance to rebel. This research also proves that there are similarities in the main characters’ development in both novels. Fahrenheit 451 by Ray Bradbury is evidently influenced by Nineteen Eighty-Four by George Orwell. Fahrenheit 451 become the other side of Nineteen Eighty-Four; or we can say that it is the American version of Nineteen Eighty-Four.Keywords: intertextuality, government control, propaganda, big brother, books banning